Prevalence of Allergy Symptoms in Schoolchildren of Chechen Republic (ISAAC Questionnaire Results) - Aset Kh. Ibisheva; Alikhan A. Idrisov; Kazbek S. Mezhidov; Leila S. Namazova-Baranova (Union of pediatricians of Russia, 2021)
Background. Rising prevalence of allergic diseases is a major medical and social problem.Objective. The aim of the study is to study the prevalence of allergy symptoms in schoolchildren of Chechen Republic according to the ISAAC (International Study of Asthma and Allergy in Childhood) questionnaire.Methods. We have surveyed 3,398 schoolchildren from 26 randomly chosen schools located in 2 urban and 2 rural areas of Chechen Republic. The first age group (7-8 years old) included 1331 first graders, the second group (13-14 years old) - 2067 eighth graders.Results. The prevalence of allergic diseases symptoms according to the questionnaire was the following: bronchial asthma (BA) - 18.4% (625 children), allergic rhinitis (AR) - 16.6% (565 children), atopic dermatitis (AD) - 4.7% (160 children), while medically verified diagnosis was established in dramatically less cases. Analysis of BA, AR, AD symptoms prevalence has revealed significant correlation between studied parameters and age. Symptoms of BA, AR prevailed in the older age group, AD in the younger one. There were no gender differences identified. Higher prevalence of BA and AR symptoms was recorded in urban residents, while the prevalence of AD in urban and rural areas was quite the same. Moreover, estimation of allergy symptoms prevalence revealed mild course of these diseases in schoolchildren of Chechen Republic.Conclusion. The study, conducted with ISAAC questionnaire, demonstrates high prevalence of allergy symptoms in schoolchildren of Chechen Republic, exceeding the official statistics. It requires particular attention from the healthcare system and improved diagnostic methods for allergies.